Graphene‐Based Porous Silica Sheets Impregnated with Polyethyleneimine for Superior CO2 Capture. (18th February 2013) - Yang, Shubin; Zhan, Liang; Xu, Xiaoyue; Wang, Yanli; Ling, Licheng; Feng, Xinliang
<x xml:space="preserve">Abstract</x> It is demonstrated that graphene‐based porous silica sheets can serve as an efficient carrier support for PEI via a simple nanocasting technology. The resulting materials possess thin nature, high PEI loading content and high thermal‐conductivity. Such features are favorable for the efficient diffusion and adsorption of CO2 as well as the rapid thermal transfer during the CO2 capture process. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>